内啮合摆线齿轮泵摆线轮齿廓参数化设计分析 - 王振; 刘忠明 (Jixie chuandong)
Internal meshing cycloidal gear pump has many advantages in application: small size、light weight、low noise、excellent self-absorption、good flow on the pulse and so on.However,because of the complex shape of tooth profile,the machining is more difficult.Base on the gear meshing principle,the equation of cycloidal gear tooth profile has been derived in the paper,and the approach of two type fillers is discussed.Using Visual Basic6.0 in AutoCAD platform,the parameter drawing of the full gear tooth curve is achieved.It is of great significance for further analysis of the meshing character and the special mechanical properties of the gear pumps.